2013
DOI: 10.1155/2013/724763
|View full text |Cite
|
Sign up to set email alerts
|

Design andIn VitroEvaluation of a New Nano-Microparticulate System for Enhanced Aqueous-Phase Solubility of Curcumin

Abstract: Curcumin, a yellow polyphenol derived from the turmeric Curcuma longa, has been associated with a diverse therapeutic potential including anti-inflammatory, antioxidant, antiviral, and anticancer properties. However, the poor aqueous solubility and low bioavailability of curcumin have limited its potential when administrated orally. In this study, curcumin was encapsulated in a series of novel nano-microparticulate systems developed to improve its aqueous solubility and stability. The nano-microparticulate sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Curcumin, a natural and crystalline compound isolated from the plant Curcuma longa, has been widely studied for its anti-inflammatory, antiangiogenic, antioxidant and anticancer effects in Chinese systems of medicine (8,9). Additionally, previous studies have shown that curcumin exhibits antiproliferative and anticarcinogenic properties in a wide variety of cell lines and animals (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a natural and crystalline compound isolated from the plant Curcuma longa, has been widely studied for its anti-inflammatory, antiangiogenic, antioxidant and anticancer effects in Chinese systems of medicine (8,9). Additionally, previous studies have shown that curcumin exhibits antiproliferative and anticarcinogenic properties in a wide variety of cell lines and animals (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro release profile showed up to 95% release of curcumin from the developed nano-microparticulate systems. 54 Akhgari et al prepared a nanosuspension formulation as a new vehicle for the improvement of the ocular delivery of vitamin A. Formulations were designed based on full factorial design. High pressure homogenization technique was employed to produce nanosuspensions.…”
Section: Colloidal Drug Delivery Systemsmentioning
confidence: 99%
“…An important study showed that encapsulating the curcumin into the hydrogel nanoparticles yielded a homogenous curcumin dispersion in aqueous solution as compared to the free form of curcumin [193] and earlier finding observed that after oral administration of CUR-PLGA-NPs, the relative bioavailability was 5.6-fold increased and also showed longer half-life compared with that of native curcumin. Increased oral bioavailability of CUR may be linked with improved water solubility, higher release rate in the intestinal juice, enhanced absorption by improved permeability, inhibition of P-glycoprotein- (P-gp-) mediated efflux, and increased residence time in the intestinal cavity [194].…”
Section: Bioavailability Of Curcuminmentioning
confidence: 99%